Understanding and managing gestational diabetes - Oats, Jeremy J. N. (Henry Stewart Talks, 2014)
Pathophysiology of gestational diabetes, Diagnostic criteria, Management of gestational diabetes, Long term-consequences for mother and child
Updated at 2014/05/12